Proportion of suicides in Denmark attributable to bereavement by the suicide of a first‐degree relative or partner: Nested case–control study. (13th September 2022) - Pitman, Alexandra; McDonald, Keltie; Logeswaran, Yanakan; Lewis, Gemma; Cerel, Julie; Erlangsen, Annette
Abstract: Objective: To provide the first estimates of the risk of suicide after bereavement by the suicide of any first‐degree relative and the proportion of suicides in Denmark attributable to suicide bereavement. Methods: We conducted a nationwide nested case–control study defining cases as all Danish‐born individuals who died by suicide in Denmark between 01 January 1980 and 31 December 2016 ( n = 32, 248), age‐matched to four living controls. Using three exposure categories (bereavement by the suicide of a relative [parent, offspring, sibling, and spouse/cohabitee]; non‐suicide bereavement; no bereavement) and conditional logistic regression adjusted for pre‐specified covariates we estimated the odds of exposure to suicide bereavement in cases versus controls. We tested whether associations differed for men and women, estimated the population attributable fraction (PAF) of suicides in our population at risk that could be attributed to a first‐degree relative's suicide loss, and estimated the attributable fraction among the exposed (AFe). Results: Suicide bereavement was associated with an increased odds of suicide when compared with no bereavement (ORadj2 = 2.90, 95% CI: 2.46–3.40) or non‐suicide bereavement (ORadj2 = 1.48, 95% CI: 1.25–1.74). There was no evidence to support any interaction with sex. PAF (0.69%; 95% CI: 0.62%–0.77%) and AFe (60.12%; 95% CI: 53.19%–66.03%) estimates suggested that in Denmark 0.69% of suicides, and 60% of suicides among suicide‐bereaved relatives, could be prevented if it was possible to address all factors increasing suicide risk in suicide‐bereaved relatives. Conclusion: Suicide bereavement in relatives and partners contributes to at least one in 145 suicides in Denmark.